2014
DOI: 10.17221/82/2014-cjgpb
|View full text |Cite
|
Sign up to set email alerts
|

Microsatellite analysis indicates the specific genetic basis of Czech bolting garlic

Abstract: Ovesná J., Leišová-Svobodová L., Kučera L. (2014): Microsatellite analysis indicates the specific genetic basis of Czech bolting garlic. Czech J. Genet. Plant Breed., 50: 226-234.Garlic, Allium sativum L., is a vegetable long used for culinary and medical purposes. A certain level of garlic quality is required by the local consumers, which is usually preserved by the varieties grown in that region. The aim was to establish an assay offering fast and inexpensive differentiation of garlic varieties. Length polym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…On the other hand, the remaining primers showed lower diversity. Ovesna et al [25] also reported that high number of allele was in accordance with high gene diversity in the study aiming to identify of Czech garlic varieties using 14 SSR markers. The number of allele and gene diversity in the present study coincided with Ma et al [26], who found the former between 2 and 9, and the latter between 0.0476 and 0.8304 in the study employing 32 accessions of V. faba and 21 microsatellite markers.…”
Section: Resultsmentioning
confidence: 86%
“…On the other hand, the remaining primers showed lower diversity. Ovesna et al [25] also reported that high number of allele was in accordance with high gene diversity in the study aiming to identify of Czech garlic varieties using 14 SSR markers. The number of allele and gene diversity in the present study coincided with Ma et al [26], who found the former between 2 and 9, and the latter between 0.0476 and 0.8304 in the study employing 32 accessions of V. faba and 21 microsatellite markers.…”
Section: Resultsmentioning
confidence: 86%
“…The primers are listed in Table 2 and include the annealing temperature and the number of detected alleles per microsatellite locus across the analysed set. PCR with fluorescently labelled primers (6-fam, vic, ned and pet; Life Technologies, Foster City, USA) was performed in a reaction as described by Ovesná et al (2014). The amplification products were separated by capillary electrophoresis in the sequencer ABI PRISM 3130 (Applied Biosystems, Foster City, USA).…”
Section: Methodsmentioning
confidence: 99%
“…The same set of cultivars was subjected to evaluation of DNA variability by the SSR length polymorphism analysis. DNA extraction was performed from leaves as identical results are obtained regardless of the tissue type used for analysis (Ovesná et al 2014). The varieties were clearly identified, and each was assigned a typical DNA profile.…”
Section: Resultsmentioning
confidence: 99%
“…Total genomic DNA was extracted from frozen pooled leaves in parallel using the CTAB (cetyltrimethylammonium bromide) method, as described by Ovesná et al (2014). DNA quality was examined by electrophoresis, and the amount was quantified by spectrophotometry.…”
Section: Methodsmentioning
confidence: 99%